Vernacular Passive Strategies for Sustainable Houses in the Andean Ecuadorian Context - Villacís Ormaza, Marcelo (2022)
Sustainability and thermal comfort in developing countries could be hard to achieve due to the high cost of standardized construction methods, such as reinforced concrete and steel framed structures. As a result, most dwellings ignore the basic principles of livability and sustainability promoting a high demand of external construction resources and using elevated quantities of energy during its operative life. The purpose of this paper is to analyze passive and vernacular strategies for typical active thermal comfort as alternatives for low rise housing in the Andean region of Ecuador by using rammed earth walls as thermal mass elements. This research aims to reach the minimum comfort levels stablished by INER and ASHRAE 90.1 envelope requirements for climate zone 4C (temperate continental).